Droop-free controls of inverter-based generator for use in systems that interconnected with synchronous generators - Suchart Janjornmanit; Sakorn Panta; Wirat Nakkrongdee (Institute of Advanced Engineering and Science, 2021)
Because of its simplicity and autonomous operation, droop control technique is widely implemented for power generation control in microgrids. Despite its popularity, it has been reported that the technique has the stability problem. In this paper, the previous work of droop-free inverter-based generator designed for operating in a fix frequency islanded microgrid, is redesigned to have the ability to operate in both islanded and grid connected microgrid as well as to the main power grid where it interconnected with synchronous generators. The proposed voltage source inverters use phase locked loop(PLL) algorithm to synchronize the changing frequency due to the operation of the synchronous generator. Unlike the frequency droop control that the output frequency is varied as its active power changed, the proposed controls do not make an adjustment of the system frequency. This kind of operation reduces the chance of the system unstable due to severe frequency change and it also reduces the frequency deviation when it increases its active power output. Simulation and result of the meshed power network demonstrate the feasibility to implement the proposed controls in thereal system.